Analysis of Teacher Perceptions Regarding the Rffectiveness of Practicum-Based Science Learning in Elementary Schools in Sorong District: Analisis Persepsi Guru Mengenai Efektifitas Pembelajaran Sains Berbasis Praktikum Pada Sekolah Dasar di Kabupaten Sorong - Soraya, Icha; Agnesa, Oki Sandra; Darmawan, Andri (IAIN Sorong, 2024)
Abstract Practicum-based science learning contributes to students' psychomotor learning outcomes, which makes it one of the methods for achieving student learning outcomes. Practical activities not only enable students to master various science process skills, but also build scientific attitudes that support the process of acquiring knowledge (science products). This research aims to determine teachers' perceptions regarding the effectiveness of practicum-based science learning in Sorong Regency elementary schools. This research is qualitative research using a descriptive approach with data collected through observation, interviews and documentation. The data sources used are primary data and secondary data, the data is analyzed through data reduction, data presentation and drawing conclusions. Interview results show that 90% of educators stated that they were ready to carry out practicum-based learning and educators believe that practicums enable students to be directly involved in the learning process and quickly understand, practicum activities are carried out using simple and adaptable tools and materials. However, during learning through practicum, many challenges arise from educators and students.